Enhanced Tomato Seed Germination and Seedling Growth Through Oxidative Stress Using Biogenic Silver Nanoparticles - Méndez-Andrade, Rolando; Ruiz-Torres, Norma A.; Wang, Yi; García-Cerdac, Luis A.; Vera Reyes, Ileana (REVISTA TERRA LATINOAMERICANA, 2024)
In this study, silver nanoparticles (AgNP) were successfully biosynthesized from Larrea tridentata leaf extract. X-ray Dif fraction (XRD) and Transmission Electron Microscopy (TEM) analysis confirmed that AgNP are crystalline and hemispherical, with sizes between 4 and 26 nm. In addition, the ef fect of nanoparticles on tomato (Solanum lycopersicum) seed germination and seedling growth was examined. Seeds were pre-soaked with dif ferent concentrations of AgNP (0, 4.03, 6.72, 18.66, 51.84, and 86.4 mg L-1). Up to 90% seed germination was achieved at a concentration of at least 4.03 mg L-1, while the control reached below 60%. The highest vigor was obtained at a concentration of 51.84 mg L-1, 2.67 times higher than the vigor of untreated seeds. The synthesized nanoparticles induced activation of tomato seedlings’ defense system against reactive oxidative species, increasing CAT and APX enzyme activities and seedling’s growth. Plumule and radicle length rose 1.49 and 1.98-fold compared to the control. The seedlings were susceptible at 86.4 mg L-1 of AgNP, which af fected all growth parameters and induced oxidative stress response through increased hydrogen peroxide (H2O2) formation and proline content. These provide further insight into the ef fects of biogenic silver nanoparticles on plants during their initial stages of development, demonstrating that these nanoparticles can promote early germination.